Exploring the Convergence of Tradition and Modernity: The Educational Tourism Potential of Suzhou Oil-Paper Umbrella Craftsmanship - Xiao Cong Jiang; Tian Yang Luo (BioResources)
Suzhou oil-paper umbrellas, as a significant part of China's intangible cultural heritage, exemplify the harmonious integration of nature and art through their intricate craftsmanship. These umbrellas are not only functional objects but also cultural symbols, reflecting centuries of traditional skills in bamboo frame making and oil-paper production. However, the preservation of these techniques faces critical challenges, including an aging artisan population, a lack of successors, and insufficient integration of local industries with cultural heritage protection efforts. The current approaches to safeguarding these crafts often focus on superficial aspects, neglecting the core techniques of bamboo processing and paper-making. This editorial considers the cultural value of Suzhou oil-paper umbrella craftsmanship, identifies the challenges in its preservation, and explores revitalization strategies through educational tourism. The research employs a comprehensive analysis of the cultural significance, current preservation efforts, and potential for sustainable development. The main contribution of this study lies in highlighting the potential of educational tourism as a vehicle for cultural heritage conservation and local economic development, providing a framework for the sustainable revitalization of this unique traditional craft.